1998
DOI: 10.1523/jneurosci.18-24-10700.1998
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Neurotrophin andtrkReceptor mRNAs in Catecholaminergic Nuclei during Chronic Opiate Treatment and Withdrawal

Abstract: The neurotrophins brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) and their receptors trkB and trkC, respectively, are expressed in the locus coeruleus (LC) and ventral tegmental area (VTA), brain regions known to be involved in opiate addiction. Previously, administration of exogenous neurotrophins has been shown to oppose effects of chronic morphine treatment on LC and VTA neurons. However, the response of endogenous neurotrophins in LC and VTA to opiate treatment is unknown. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
74
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 53 publications
4
74
2
Order By: Relevance
“…In rat A6 neurons, NT-3 expression was increased after chronic morphine exposure but fell below baseline levels after acute withdrawal. 5 The high affinity receptor for NT-3, trkC, also shows dynamic changes in expression during chronic opiate exposure and withdrawal. 5 These studies suggested indirectly that NT-3, by affecting noradrenergic neuronal function, modulates opiate addiction and withdrawal behaviors.…”
Section: Reduced Opiate Withdrawal In Conditional Mutants Is Accompanmentioning
confidence: 99%
See 2 more Smart Citations
“…In rat A6 neurons, NT-3 expression was increased after chronic morphine exposure but fell below baseline levels after acute withdrawal. 5 The high affinity receptor for NT-3, trkC, also shows dynamic changes in expression during chronic opiate exposure and withdrawal. 5 These studies suggested indirectly that NT-3, by affecting noradrenergic neuronal function, modulates opiate addiction and withdrawal behaviors.…”
Section: Reduced Opiate Withdrawal In Conditional Mutants Is Accompanmentioning
confidence: 99%
“…Molecules of the nerve growth factor family may influence neuronal health and plasticity both in the developing and in the adult brain, including the reward and addiction circuitry. 4 Brainstem noradrenergic neurons of the adult rodent and primate brain express the neurotrophin-3 (NT-3) high affinity receptor, TrkC, [5][6][7] as well as the brain derived neurotrophic factor (BDNF) and neurotrophin-4/5 (NT-4/5) receptor TrkB. In selected neuronal populations, NT-3 may promote growth and survival by binding to TrkB or TrkA, the high affinitity receptor for nerve growth factor (NGF).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some authors have specifically questioned the involvement of NT3 in prenatal LC development since Nt3-or double Gdnf/Nt3-null mutant mice (Ernfors et al, 1994;Fariñas et al, 1994;Holm et al, 2003) do not display clear developmental abnormalities in this region. Neurons of the LC, express high levels of neurotrophin type-2 TrkB (NTRK2-Mouse Genome Informatics) and neurotrophin type-3 receptor TrkC (NTRK3-Mouse Genome Informatics) (Numan et al, 1998;King et al, 1999). However, it remains to be determined whether TrkC ligands regulate the development of LC NA neurons in vivo and if developmental alterations in LC may facilitate an anxiety prone phenotype and predispose to the development of panic disorder.…”
mentioning
confidence: 99%
“…For morphine tolerance, NT4 may be acting in regions relevant to addiction, such as the nucleus accumbens and locus coeruleus. Interestingly, BDNF and NT3, as well as their receptors trkB and trkC, show expression changes in the locus coeruleus as a result of both morphine withdrawal and chronic administration [11].…”
mentioning
confidence: 99%